1975
DOI: 10.1111/j.1476-5381.1975.tb06940.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Pancreatic Secretion‐dynamics of Subcellular Calcium Pools in Resting and Stimulated Acinar Cells

Abstract: I Pulse-chase experiments were carried out on pancreatic tissue lobules incubated in vitro, with 45Ca as the tracer, in order to shed some light on the functional significance of the calcium pools associated with the various cell organelles of the acinar cell, especially in relation to stimulus-secretion coupling. 2 The kinetics of tracer uptake and release which were observed in the intact lobules suggest the existence of a number of intracellular pools, whose rate of exchange is slower than that across the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

1976
1976
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 48 publications
0
10
0
2
Order By: Relevance
“…Clemente a(I Nleldolesi (28) have found that in homiiogeniates of intact guinlea pig pancreas, the distribution of tisstse calciumiii is: zym ogen granutiles, 35%; zyvimogenl granule membranes, 6%; plasmia meml)ranes, 5%; iuiitochondclria, 6%; imiicrosomiies, 19%. In a subsequent studx (22) 45 Ca during lvsis aind filtration wvill result not onlv in underestimation of the fraction of total cellular 45Ca that is membrane-bound but also in overestimation of the fraction that is free. 4 Wlhat ve have calculated as "free cellular 45Ca" should not be interpreted to mean "cytoplasmic 45Ca", siince our techni(ue does not distinguish between radlioactivity free in the cytoplasm and free but localized to anatomiically defined cellular comppartments sutcl as mitochondria, nuclei, or zymlogen granules.…”
Section: Totalmentioning
confidence: 99%
“…Clemente a(I Nleldolesi (28) have found that in homiiogeniates of intact guinlea pig pancreas, the distribution of tisstse calciumiii is: zym ogen granutiles, 35%; zyvimogenl granule membranes, 6%; plasmia meml)ranes, 5%; iuiitochondclria, 6%; imiicrosomiies, 19%. In a subsequent studx (22) 45 Ca during lvsis aind filtration wvill result not onlv in underestimation of the fraction of total cellular 45Ca that is membrane-bound but also in overestimation of the fraction that is free. 4 Wlhat ve have calculated as "free cellular 45Ca" should not be interpreted to mean "cytoplasmic 45Ca", siince our techni(ue does not distinguish between radlioactivity free in the cytoplasm and free but localized to anatomiically defined cellular comppartments sutcl as mitochondria, nuclei, or zymlogen granules.…”
Section: Totalmentioning
confidence: 99%
“…It has been known for more than 20 years that they contain large amounts of total calcium (20-60 mM), in particular chromaffin granules of the adrenal medulla and zymogen granules of the exocrine pancreas [1][2][3]. In addition, chromaffin granules contain also large amounts of proteins (100 mg/ml, of which 40% is chromo- granin A), catecholamines (0.5-0.6 M) and ATP (130 mM) [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…This high calcium content is not exclusive of chromaffin granules but instead it is also found at similar or even higher values in most types of secretory granules, e.g. zymogen granules of pancreatic acinar cells [15], small synaptic vesicles of the neuromuscular junction [13], insulin granules [16] and many others (see [17] for a review).…”
Section: The Problem Of the Free And Total Calcium Concentration In Tmentioning
confidence: 91%
“…In the case of the secretory granules, some reports suggest that at least part of the stored calcium is relatively immobile or exchanges very slowly with the free Ca 2+ pool. Clemente and Meldolesi [15] found that zymogen granules have a very slow rate of 45 Ca accumulation and release compared with other organelles, suggesting that the stored Ca 2+ could play mainly a structural role in the architecture of the organelle. Similarly, 45 Ca flux experiments performed in PC12 cells showed that the granule Ca 2+ pool was extraordinarily stable in periods of hours in EGTA-containing medium, and very slow to label [14], concluding that the stored Ca 2+ would only serve to keep granule components together and to be discharged to the extracellular space by exocytosis.…”
Section: The Problem Of the Free And Total Calcium Concentration In Tmentioning
confidence: 99%